2020
DOI: 10.30737/ekonika.v5i2.1129
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Customer Relationship Marketing dan Kualitas Layanan Terhadap Kepuasan : Studi Konsumen McDonald’s Kediri

Abstract: McDonald's is a fast food restaurant that has a branch in Kediri. The restaurant currently has competitors that can reduce customer satisfaction. Therefore, the research conducted aims to determine the partial and simultaneous effects of using the independent variables Customer Relatioship Management and Service Quality and the dependent variable Customer Satisfaction. The sample used in this study was 93 respondents using the Slovin formula. Based on the results of the study, the characteristics of the domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
1
3
0
3
Order By: Relevance
“…This study's findings logically support Laely's conclusions that consumer connections and service quality positively and significantly impact consumer satisfaction [24]. Mayasari's research found that time management and total quality service at the Obstetrics and Gynecology Polyclinic RSIA Anugrah Medical Center substantially impacted patient satisfaction [25].…”
Section: Tqs Variable Correlation Test To Consumer Satisfaction Variablesupporting
confidence: 78%
“…This study's findings logically support Laely's conclusions that consumer connections and service quality positively and significantly impact consumer satisfaction [24]. Mayasari's research found that time management and total quality service at the Obstetrics and Gynecology Polyclinic RSIA Anugrah Medical Center substantially impacted patient satisfaction [25].…”
Section: Tqs Variable Correlation Test To Consumer Satisfaction Variablesupporting
confidence: 78%
“…Hasil penelitian (Sembiring, Diamond & Yulia, 2020), (Suwarsito & Aliya, 2020), (Hilman, Siti & Marlena, 2020). (Hendrian Yonata , Priski Setiawan, Ruby Santamoko, Dodi Ilham, 2020), (Nur Laely, Djunaedi, 2020), menyatakan bahwa kualitas pelayanan dapat meningkatkan kepuasan konsumen. (Holotová, 2020).…”
Section: Pendahuluanunclassified
“…Relationship marketing is not just about providing services at the place, time, and price demanded by the target market, but it wants to build relationships with the target market that will buy from it again in the future and encourage others to do so. Relationship marketing seeks to retain more customers and lose fewer customers [19]. Researchers have linked three factors to the popularity of relationship marketing in the late 1990s.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…By increasing loyalty, customer satisfaction guarantees future earnings, reduces the cost of future transactions, reduces price flexibility, and minimizes the likelihood that customers will slip in the face of disadvantages [27]. Customer satisfaction is widely considered as a key effect in shaping customers' future purchasing intentions [19].…”
Section: Customer Satisfactionmentioning
confidence: 99%